Development of new self-assembled cationic amino liposomes for efficient gene delivery. (23rd April 2020) - Wu, Yihang; Xiong, Yue; Wang, Ling; Zhou, Quanming; Li, Linxian; Levkin, Pavel A.; Davidson, Gary; Gao, Liqian; Deng, Wenbin
Abstract : A library of lipidoids self-assembling to liposomes exhibits excellent transfection efficiency in HEK 293T cells and mESCs with low cytotoxicity. Abstract : A library of 83 structurally diverse cationic amino liposomes is rationally designed and parallelly synthesized for the transfection of plasmid DNA and siRNA. Our designed self-assembled liposomes not only exhibit excellent transfection efficiency in HEK 293T cells and mouse embryonic stem cells, but also show low cytotoxicity.